A Novel Lipoate-Protein Ligase, Mhp-LplJ, Is Required for Lipoic Acid Metabolism in Mycoplasma hyopneumoniae - Jin, Jin; Chen, Huan; Wang, Ning; Zhu, Kemeng; Liu, Huanhuan; Shi, Dongfang; Xin, Jiuqing; Liu, Henggui (Frontiers in Microbiology, 2021)
Lipoic acid is a conserved cofactor necessary for the activation of several critical enzyme complexes in the aerobic metabolism of 2-oxoacids and one-carbon metabolism. Lipoate metabolism enzymes are key for lipoic acid biosynthesis and salvage. In this study, we found that Mycoplasma hyopneumoniae (M. hyopneumoniae) Mhp-Lpl, which had been previously shown to have lipoate-protein ligase activity against glycine cleavage system H protein (GcvH) in vitro, did not lipoylate the lipoate-dependent subunit of dihydrolipoamide dehydrogenase (PdhD). Further studies indicated that a new putative lipoate-protein ligase in M. hyopneumoniae, MHP_RS00640 (Mhp-LplJ), catalyzes free lipoic acid attachment to PdhD in vitro. In a model organism, Mhp-LplJ exhibited lipoate and octanoate ligase activities against PdhD. When the enzyme activity of Mhp-LplJ was disrupted by lipoic acid analogs, 8-bromooctanoic acid (8-BrO) and 6,8-dichlorooctanoate (6,8-diClO), M. hyopneumoniae growth was arrested in vitro. Taken together, these results indicate that Mhp-LplJ plays a vital role in lipoic acid metabolism of M. hyopneumoniae, which is of great significance to further understand the metabolism of M. hyopneumoniae and develop new antimicrobials against it.